2017
DOI: 10.1177/1461355717711453
|View full text |Cite
|
Sign up to set email alerts
|

White-collar crime

Abstract: Policing religious organizations presents challenging situations. When there is suspicion of financial crime by white-collar criminals, secrecy and trust represent obstacles to law enforcement. This article discusses the lack of detection and neutralization techniques often applied in religious organizations. There may be too much trust, too much freedom, too much individual authority, too little scepticism, too much loyalty and too little control of the financial side in religious organizations. There may be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 15 publications
(25 reference statements)
0
1
0
Order By: Relevance
“…A test of convenience theory by survey research will need to distinguish different kinds of organizations. For example, Gottschalk (2017) found that religious institutions tend to have members with weaker personal willingness to commit financial crime, while the organizations themselves offer greater opportunities to commit and conceal financial crime. Other kinds of organizations -such as museums, family-owned enterprises, small and medium-sized business versus multinational corporations, and public organizations -will all have different and special characteristics.…”
Section: Survey Statementsmentioning
confidence: 99%
“…A test of convenience theory by survey research will need to distinguish different kinds of organizations. For example, Gottschalk (2017) found that religious institutions tend to have members with weaker personal willingness to commit financial crime, while the organizations themselves offer greater opportunities to commit and conceal financial crime. Other kinds of organizations -such as museums, family-owned enterprises, small and medium-sized business versus multinational corporations, and public organizations -will all have different and special characteristics.…”
Section: Survey Statementsmentioning
confidence: 99%